TEACHING ENGLISH AT THE SIXTH YEAR OF SDN 4 JUWORO - Arifana, Hidayah Eka (2010)
This research paper is intended to describe the techniques of teaching English used by the teacher in SDN 4 Juworo. This research paper also describes the problem faced by the teacher and the students in teaching and studying English. The researcher does three ways to collect the data, namely: observation, interview, and document. The data are field notes that are taken from teaching-learning process, note of interview with the teacher about the techniques used and document to support teaching English. In collecting the data, the writer focuses on the sixth year of SDN 4 Juworo. The result of the observation shows that, (1) there are two techniques used in teaching English to the sixth year of SDN 4 Juworo namely: picture observation and jumbled words. Both of those techniques are applied to make the students interested in learning English, (2) there are many problems faced by the teacher in teaching English namely: limited vocabulary, pronunciation, and motivation. The problem solving of those problem are: in limited vocabulary, the teacher gives a list of difficult words related to the topic. In pronunciation, the teacher gives example how to read the words in English correctly and the students repeat and memorize it. In motivation, the teacher should gives motivate the students in order that they are confidence to express their idea. Beside the problems faced by the teacher, (3) there are many problems faced by the students in studying English namely: student's interest and material. The problems solving of those problem are: the students must have an intention to know about foreign language and teacher should give material according to their ability and their level.